A Preliminary Study of the Attitudes and Barriers of Family Physicians to Prescribing HIV Preexposure Prophylaxis - Ojile, Nicholas; Sweet, Donna; Kallail, K. James (Kansas Journal of Medicine, 2019)
Introduction. Attitudes of individuals who provide HIV caretowards prescribing Preexposure Prophylaxis (PrEP) to at-riskpopulations have been studied, but few studies indicate if familyphysicians would be willing to prescribe PrEP as most familyphysicians do not specialize in HIV medicine. Few data existon the perceived barriers preventing family physicians fromprescribing PrEP. The purpose of this project was to assess theattitudes and perceived barriers of family physicians in Kansastowards prescribing PrEP to high risk patient populations.Methods. This study was a descriptive, observational,and cross-sectional survey of family physicians who respondto email surveys issued through the Family MedicineResearch and Data Information Office (FM RADIO).Results. Fifty-three percent of family physicians take a sexualhistory on new patients less than frequently, and only35% frequently ask about the use of safe sex practices. Only29% frequently ask if the patient has sex with men, women,or both. Seventy-six percent of respondents would be willingto prescribe PrEP to men who have sex with men, and anequal percentage would be willing to prescribe to heterosexuallyactive men and women who are at substantial risk of acquiringHIV. While 59% of participants agreed that PrEP belongsin the primary care domain of treatment, 71% agreedthat they had limited or no knowledge of PrEP guidelines.Conclusions. This preliminary study indicated a need for increasedfamily physician screening of new patients for high risksexual behaviors who would be eligible for PrEP. The limitedknowledge of PrEP guidelines and its use in clinical practiceare significant limiting factors to increasing prescribing practicesin the family medicine community rather than a perceivedethical dilemma of prescribing PrEP to men who have sex withmen. As a result, an increase in continuing medical educationabout PrEP could significantly increase its prescribing inthe family medicine community. KS J Med 2017;10(2):40-42.